2016
DOI: 10.1136/bmjopen-2015-010933
|View full text |Cite
|
Sign up to set email alerts
|

Does case management for patients with heart failure based in the community reduce unplanned hospital admissions? A systematic review and meta-analysis

Abstract: ObjectivesThe aim of this systematic review of randomised controlled trials (RCTs) and controlled trials (non-RCTs, NRCTs) is to investigate the effectiveness and related costs of case management (CM) for patients with heart failure (HF) predominantly based in the community in reducing unplanned readmissions and length of stay (LOS).SettingCM initiated either while as an inpatient, or on discharge from acute care hospitals, or in the community and then continuing on in the community.ParticipantsAdults with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 47 publications
2
65
0
3
Order By: Relevance
“…A recent systematic review has concluded that hospital‐initiated case management continuing in the community for patients with heart failure can reduce subsequent unplanned admissions and hospital length of stay (Huntley et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review has concluded that hospital‐initiated case management continuing in the community for patients with heart failure can reduce subsequent unplanned admissions and hospital length of stay (Huntley et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…These approaches are thought to be key to reducing admissions (Boren, Wakefield, Gunlock, & Wakefield, ; Ditewig, Blok, Havers, & van Veenendaal, ; Jovicic, Holroyd‐Leduc, & Straus, ). However, few case managements for heart failure trials focused on the mechanisms for the better monitoring of signs and symptoms, although a minority describe components such as patient‐directed access, referral to other services, assessment of home environment and emotional support (Huntley, Johnson, King, Morris, & Purdy, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, systematic reviews have shown that case management resulted in statistically significant reductions in hospital utilization, including days in hospital, and in increased quality of and satisfaction with care (Huntley et al. ; Joo & Liu ; You et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…And Huntley et al. () found that hospital‐initiated case management was strongly associated with reducing hospital readmission for heart failure. You et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation